The use of informational technology for sustainable development: implications for students with different levels of life meaningfulness - Grishina Anastasia; Dyakova Elena; Pronenko Evgeny; Ismailov Ismail (E3S Web of Conferences, 2022)
The article is devoted to the study of the relationship between the fact of violation of psychological boundaries, as a consequence of active using of informational technologies in everyday life, the level of meaningfulness of life and coping strategies of students. The authors indicated the relevance of the study, analyzed theoretical approaches to the phenomenon of violation of psychological boundaries, as a consequence of the active use of informational technologies in the context of meaningful life and coping strategies. The article describes the procedure of empirical research. It has been shown that students with medium and high levels of meaningfulness of life have a tendency to expand the boundaries in the process of communication in the informational space. It was revealed that the leading behavioral strategy of students who are prone to psychological dependence on informational technologies, expressed in the impossibility of refusing them, as well as in their subjective significance, are the strategies of escape and avoidance of problem situations in real life. The study of the relationship between coping strategies and violation of psychological boundaries has shown that non-adaptive strategies of behavior and response, expressed in ignoring real problems, have a strong positive relationship with the active escape of students into the informational space, as well as an average positive relationship with expanding the boundaries of communication on the Internet.